Primary non-Hodgkin's Lymphoma of Breast- A Rare Entity - Aishvarya Jandial; Subhash Bhardwaj; Surbhi Mahajan (Dr. Annil Mahajan, 2022)
Malignant lymphoma is a neoplastic entity which originates in lymphatic tissue. Primary breast lymphoma is a rare and distinct possibility in the diagnosis of breast malignancies. We, here, report a case of primary breast lymphoma in a 45 years old female. The presumptive diagnosis was made on fine needle aspiration cytology which was later on confirmed on histology after lumpectomy. The histology and immunohistochemistry were in accordance with non -Hodgkin's lymphoma. Since the prognosis, management and outcome of primary breast lymphoma is totally different from that of carcinoma so, the clinicians treating breast carcinoma cases should be aware of this rare entity.